Characterisation of blackwater from human transportation systems equipped with vacuum toilets and controlled emissions tanks and its impact on solid/liquid separation technologies - Jadhav, N.; Brown, Tim; Williams, Leon; Pidou, Marc (Elsevier, 2024)
The first ever detailed characterisation of blackwater from human transportation systems equipped with vacuum toilets and Controlled Emissions Tanks (CET) revealed a stream that is very concentrated in salts and nutrients when compared to other blackwater sources. Escherichia Coli (E. coli) levels in the blackwater characterised were comparatively lower than the range reported for septic tanks, for example. Suspended solids were significantly lower than the levels found in pit latrines, but closely comparable to those reported for gravity toilets. The average COD of 3566 ± 2049 mg/L was typically lower than in pit latrines and gravity flush toilets. These findings then show that the characteristics of the blackwater from human transportation systems are directly impacted by a combination of the low flush vacuum toilets, storage in the CET, and different behaviour for passengers with increased usage for urination over defecation when compared to common uses of toilets. Such factors collectively dictate the nature of the blackwater and require that a solid/liquid separation technology for further processing is fundamentally robust in operation. The greater solids pulverisation, largely resulting from vacuum flushing combined with the storage environment, reduces the suitability of centrifugal and settling technologies whilst making filtration the most suitable option.
Keywords: 40 Engineering; 4004 Chemical engineering; 4005 Civil engineering; 4011 Environmental engineering; Blackwater; Controlled emission tanks; Faeces; Separation; Wastewater